Law enforcement activity, globalization and social morality in frameworks of mass culture (On the Example of Modern European TV-Shows on Law-Enforcements. Part 2) - Vovk V. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The article discloses the organic interrelationship of globalization processes, mass culture phenomena, social morality, and the peculiarities of law enforcement activities through mass culture, in TV series. The author outlines a wide range of questions devoted to the interaction of various spheres of a person's spiritual life (social morality, law, law enforcement, art), which has great variability, is represented by a wide palette of subject forms, reflects the current social reality and at the same time constructs it. Cultural and semiotic methodological approaches assisted in carrying out an analysis of modern series on law enforcement officers to find in them the transmission of the main moral values of Western European society, which include humanism, equality, tolerance, and inclusion. Methodology. The methodology includes a comprehensive analysis and a synthesis of available scientific and theoretical information. It is includes the formulation of relevant conclusions and recommendations. Special attention is paid to analyzing the sociocultural context within which modern mass culture exists (globalization, the spread of democracy, unification and standardization of life, compression of time, significant information flow, clip type of thinking, etc.). Results: the article shows that the spread of mass culture is due to the development of technologies and a change in the type of communication: from verbal-written to audiovisual (which only confirms the fundamental importance of sight and visual metaphor within European culture). Originality. The article focuses on the fact that modern series about the work of law enforcement officers reflect the realities of modern Western European society, which overcomes the fear of the other with the help of the affirmation of moral values and their legal support; recognizes equality both in the field of opportunities and in the field of responsibility; forms and approves new gender and social models of behavior, keeping the values of individualism and person-centeredness effective; recognizes the special role of civil society institutions in monitoring the activities of state bodies, including law enforcement. Due to the rapid development of technologies and accessibility, the series as a screen form performs an informative function, introducing the viewer to basic social, moral, and legal values